DAMPAK EKONOMI PEMUTUSAN HUBUNGAN DIPLOMATIK RUSIA DENGAN TURKI TAHUN 2016 TERHADAP PEREKONOMIAN TURKI - Dodi Berlin Tindaon; Faisal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This paper describes the impact of Russia's 2016 diplomatic termination on Turkey over the tragedy of Russian FU-24 firing by Turkish military in Turkey's border region with Syria by 2015. The severance of diplomatic ties is marked by Russia's economic sanctions for Turkey. Economic sanctions issued by Russia include a reduction in Turkish imports exports to Russia, the cancellation of Russian travel packages to Turkey, shutting down Turkish-owned plant operations in Russia, suspension of the Turkish-Russian Visa-free cooperation, stopping the ongoing Turkish-Russian mega project in the previous year. Upon the issuance of Russian economic sanctions, it has had an impact on Turkey's economy and politics. Considerable impacts are the decline of Turkey's imported exports to Russia, the declining number of Russian tourists to Turkey, the non-operation of Turkish-owned factories in Russia, the slowdown of the Turkish-Russian construction project. The shooting incident also affects the political relations between the two countries. Not only that, the stretching of the Turkish-Russian relations provided an opportunity for separatist groups to stage a coup in Turkey. But in the end, at the instigation of mutual interest, the Turks returned to improve relations between the two countries for common interests and goals even though Turkey had experienced a decline in economic growth and political stability of Turkey.Keywords: Diplomatic ties, economic sanctions, Russian FU-24 Shooting, Foreign policy